Chemokines: A New Dendritic Cell Signal for T Cell Activation - Thaiss, Christoph A.; Semmling, Verena; Franken, Lars; Wagner, Hermann; Kurts, Christian (Frontiers in Immunology, 2011)
Dendritic cells (DCs) are the main inducers and regulators of cytotoxic T lymphocyte (CTL) responses against viruses and tumors. One checkpoint to avoid misguided CTL activation, which might damage healthy cells of the body, is the necessity for multiple activation signals, involving both antigenic as well as additional signals that reflect the presence of pathogens. DCs provide both signals when activated by ligands of pattern recognition receptors and “licensed” by helper lymphocytes. Recently, it has been established that such T cell licensing can be facilitated by CD4+ T helper cells (“classical licensing”) or by NKT cells (“alternative licensing”). Licensing regulates the DC/CTL cross-talk at multiple layers. Direct recruitment of CTLs through chemokines released by licensed DCs has recently emerged as a common theme and has a crucial impact on the efficiency of CTL responses. Here, we discuss recent advances in our understanding of DC licensing for cross-priming and implications for the temporal and spatial regulation underlying this process. Future vaccination strategies will benefit from a deeper insight into the mechanisms that govern CTL activation.